Democracy and Political Violence in Nigeria Since Multi -Party Politics in 1999: A Critical Appraisal - Igwe Prince Ikechukwu (De Gruyter, 2021)
The return to democracy in Nigeria in 1999 ushered in some form of political reforms, particularly in the conduct of multi- party elections however political violence appears perverse. The objective of this study is to explore how the prevalence of political violence has undermined Nigeria’s democracy. The analysis follows survey data to address the questions regarding democracy and political violence. The study draws from the frustration-aggression and group violence theories and provides a deepened analytic exploration. Based on some of the assumptions of democracy understood as freedom, equality, accountability, rule of law etc, the study argues that these assumptions obviously constitute a ‘universal pattern’ in democratic practice, which makes a critical evaluation of the Nigerian experience important. Consequently, our findings suggest that the prevalence of political violence is fundamentally an attribute of vested interests of the political elite. Some policy recommendations follow.